Evaluation Batch Process Scheduling for Single Campaign in FMCG Industry - Anugraha, Rendra Panca; Tirtadinata, Jacqueline; Hansell, Delvin Theodorus; Rahayu, Sisilia Kusuma; Sari, Anggraeni Puspita; Arifin, Rizal; Pratiwi, Vibianti Dwi; Handogo, Renanto (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2023)
The Fast-Moving Consumer Goods (FMCG) sector plays a pivotal role in meeting daily consumer requirements. Efficient manufacturing and revenue generation are of paramount importance. The industry adopts a batch-processing approach to maintain adaptability and responsiveness to evolving market needs. A critical element in this process is the evaluation of batch scheduling, especially the batch cycle time of the products, a key factor with a substantial impact on production efficiency and profitability. This research delves deep into the complexities of batch scheduling methods between overlapping batches and parallel units for limiting steps, especially single-product campaigns in terms of its benefit towards production efficiency and company profitability. In the end, it illustrates the consequences of optimal scheduling on production time and income, highlighting the potential for significant improvements or downwards within the applied method through sensitivity analysis, which could give the FMCG industry more careful consideration in strategizing its future planning production